IMPLEMENTASI PERMAINAN MENANGKAP BOLA PADA KELENTURAN DAN KOORDINASI OTOT JARI DAN TANGAN ANAK USIA 2 - 3 TAHUN - Mahkamah Brantasari; Andi Aslindah (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2018)
Children aged 2-3 years is a child whose motor development is very rapid, so it is necessary to conduct activities to train children motor, motorik should be directed and trained in some activities that are implemented in the game to catch the ball so that flexibility and coordination of finger muscles and hands of children develop in thorough in accordance with the maturity of the child itself. This study was conducted on 3 children aged 2-3 years who have not been able to catch the ball well, so the practice of catching the ball that is divided into three sessions that is close to the ball with a distance of 60 cm, the second using the technique five times catch the ball, but with the distance increased to 90 cm, and the third catch the ball that adds up to ten times but with the same distance of 90 cm until the child can catch the ball well. The game research catches the ball executed with a 15 hour time for 15 days in the live researcher's environment. In the results of this case study seen the movement between flexibility and finger muscle coordination began to wake up. This ability is influenced by the practice of catching the ball that is often done so that the child's body position and hands become flexible to catch every ball thrown at him. This of course adds to the child's concentration power, thinking power, skills, confidence and happiness in children. The more often a child practicing catching the ball the better the attitude and posture that the child has.